The effect of parity conservation on the spin-orbit conserving and spin-orbit changing differential cross sections for the inelastic scattering of NO(X) by Ar. - Eyles, C; Brouard, M; Chadwick, H; Aoiz, F; Kłos, J; Gijsbertsen, A; Zhang, X; Stolte, S (2012)
The fully Λ-doublet resolved state-to-state differential cross sections (DCSs) for the collisions of NO(X, (2)Π, v = 0, j = 0.5) with Ar have been shown to depend sensitively on the conservation of the total parity of the NO molecular wavefunction. Parity changing collisions exhibit a single maximum only in the DCS, while parity conserving transitions exhibit multiple rainbow peaks. This behaviour is shown to arise directly from the constructive or destructive interference of collisions impacting on the two pointed ends and on the flatter middle of the NO molecule. A simple hard shell, four path model has been employed to determine the relative phase shifts of the paths contributing to the scattering amplitude. The model calculations using the V(sum) potential, together with the results of a quasi-quantum treatment, provide good qualitative agreement with the experimental spin-orbit conserving (ΔΩ = 0) DCSs, suggesting that the dynamics for all but the lowest Δj transitions are determined largely by the repulsive part of the potential. The collisions leading to spin-orbit changing transitions (ΔΩ = 1) have been also found to be dominated by repulsive forces, even for the lowest Δj values. However, they are less well reproduced by hard shell calculations, because of the crucial participation of the V(diff) potential in determining the outcome of these collisions.